PENGARUH KNOWLEDGE, SKILL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. LUSIANA JASA KARYA PERTAMINA MOR IV SEMARANG - Wahyudi, Dhevina; Yuliati, Yuliati (STIE PENA, 2022)
Decreased employee performance indicates that employees still lack knowledge, skills and work motivation. This study was structured to determine the effect of knowledge, skills and work motivation on employee performance at PT. Lusiana Jasa Karya. The population is 350 people and the sample is 187 people. Data analysis using multiple linear regression test while to see the level of significance either partially or simultaneously used t test and also f test. The results showed that (Knowledge) (X1), Skill (X2) and Work Motivation (X3) both partially and simultaneously had a significant influence on the dependent variable, namely Employee Performance of PT. Lusiana Jasa Karya.Keywords: Knowledge, Skill, Work Motivation, Employee Performance